A Review of Existing Transtibial Bionic Prosthesis: Mechanical Design, Actuators and Power Transmission - Ade Reza Ismawan; Tony Prahasto; Mochammad Ariyanto; Budi Setiyana; Robin Novriansyah (Journal of Biomedical Science and Bioengineering, 2021)
Transtibial and transfemoral amputations are the most common amputations in the world, loss of lower extremity result in impaired function extremities and also body balance. A prosthesis is a medical device designed to replace a specific body part to restore function to a body part lost due to an accident or disease. Most doctors strongly recommend the use of a prosthesis so that patients can return to normal activities after undergoing an amputation. Besides functioning to support beauty, the use of prostheses is also to restore the quality of life of prosthetic users, the issue of metabolic energy consumption when walking is also very important in designing transtibial bionic prosthesis because it involves the comfort of the user transtibial prosthesis. Most of the existing transtibial prosthesis products in Indonesia are conventional passive transtibial foot products, and passive prosthesis users show a limp or asymmetrical gait pattern so that conventional passive prosthesis users experience discomfort when walking in the form of pain in the amputated leg and normal foot, which can cause secondary musculoskeletal injuries such as joint disorders. Passive prostheses cannot generate propulsive force during push-off phase (terminal stance and preswing) of the human gait cycle. The use of passive prostheses can also consume 20-30% more metabolic energy while walking so that it can cause fatigue for the user. Transtibial bionic prosthesis research is growing, transtibial bionic prosthesis can overcome the weakness of passive prosthesis because it can produce push-off during gait cycle and several researchers have shown that bionic prostheses are capable of mimicking the human gait, as well as improve the  performance in a more natural gait and normal walking. This study aims to study the existing transtibial bionic prosthesis by comparing between 6 existing designs of powered ankle or transtibial bionic prosthesis that have been published in several publications. The discussion focuses on the design and mechanical systems, actuators related to the selection of motors and drive mechanisms as well as power transmission from actuators to moving components.